ESRA19-0626 Prolonged analgesic duration of brachial plexus block by addition of dexamethasone to dexmedetomidine for sedation. (30th August 2019) - Hong, B; Kim, B; Yun, S; Youngkwon, K
Abstract : Background and aims: We previously reported that dexmedetomidine for sedation prolonged analgesic duration of brachial plexus block (BPB). However, the prolonged effect was limited only on the day of surgery and this led to severe pain during the night and sleep disturbance. We hypothesized that co-administration of dexamethasone with dexmedetomidine for sedation could significantly prolong the analgesic duration of BPB. Methods: 60 patients received supraclavicular BPB and randomly assigned to one of three groups: C group (Control, midazolam), DM group (Dexmedetomidine), DMDX group (Dexmedetomidine + Dexamethasone 10 mg). Primary outcome was ratio of patients whose analgesic duration extended to 20 hours and time to first request for analgesia by survival analysis. Quality of sleep and pain score were also measured as secondary outcomes. Results: There was no case that the effective analgesic duration was over 20 hours in C and DM groups. Only 12 patients (60.0%) were in DMDX group. Time to first request for analgesia (median [interquartile range]) was significantly longer in DMDX group (24.0 [16.5, -] hours) than in DM and C groups (10.5 [9.0, 14.0] and 7.0 [7.0, 8.0] hours) (P < 0.001). Even though the rate of sleep disturbance on POD 0 was insignificant among 3 groups, DMDX group showed the better score of sleep quality than other 2 groups. Postoperative maximum NRS pain score in DMDX group was significantly lower than in other two groups. Conclusions: The addition of dexamethasone to dexmedetomidine for sedation in BPB seems to increase analgesic duration significantly and provide a favorable sleep quality to patients.